A novel bidirectional DC–DC converter with high voltage conversion ratio and capability of cancelling input current ripple - Kazem Farajzadeh; Leila Mohammadian; Sima Shahmohammadi; Taher Abedinzadeh (IET Power Electronics, 2024)
Abstract This paper proposes a novel bidirectional DC–DC converter with high voltage conversion ratio and capability of cancelling input current ripple. The proposed converter uses two coupled inductors and switched‐capacitor circuit to increase the voltage conversion ratio. The input current ripple at low voltage side can be eliminated for a pre‐selected duty cycle by adjusting special values of magnetizing inductances of coupled inductors. The input current is divided into two paths of the primary winding of coupled inductors that causes the decrease in the current stresses of switches. The proposed converter has five switches that consist the internal diodes of switches to bring about bidirectional power flow and have boost and buck operations. Here, the proposed topology is analysed in all operating modes and the current and voltage stresses of switches, input current ripple cancelling condition and voltage conversion ratio are calculated. Finally, the accuracy performance of the proposed converter is reconfirmed through EMTDC/PSCAD simulation and experimental results for boost operations.